Amnestic dementia impairment in Parkinson's disease: The role of body composition, ageing and insulin resistance. (August 2017) - Schelp, Arthur Oscar; Mendes-Chiloff, Cristiane Lara; Paduan, Vanessa Cristina; Corrente, José Eduardo; Vieira, Aline; Marchette, Juliana Cristine Nunes; de Souza, Juli Thomaz; Luvizuto, Gustavo José; Nogueira, Célia Regina; Bazan, Rodrigo
Summary: Background: The risk of cognitive impairment associated with Parkinson's disease (PD) is related to ageing. The role of body compartmentalization and associated metabolic dysfunctions, as a risk factor for dementia in PD is still not clear. Objective: To investigate body mass distribution, insulin resistance, and other parameters in patients without dementia, and those with dementia classified as compromised delayed memory. Subjects and Methods: We recorded body composition, basal levels of insulin resistance, and other data from 135 patients, who were followed for at least two years. The patients completed a Brief Cognitive Battery test. Patients with delayed recall memory impairment were assessed using the Mattis dementia rating scale. Results: There was a correlation between age and the patient's scores. Age was negatively correlated with scores on all of the screening battery subtests (p ≤ 0.001), while formal education was positively correlated with the test scores. Insulin resistance was higher in non-demented patients compared to patients with impaired memory (p = 0.0027). There was no association between body composition and cognitive dysfunction in patients with PD. Conclusions: The results of this study indicate an apparent decrease in insulin resistance associated with cognitive impairment in PD. We found no correlations between body composition and memory dysfunction associated with PD. Highlights: The influence of nutritional disorders and fat accumulation in PD outcome is not confirmed. This study no demonstrates correlation between body distribution and memory in PD patients. The study demonstrates low insulin resistance in PD patients with cognitive disturbances. The apparent protective effect of same metabolic responses in PD patients was not clarified.